Wakefield excitation in nonlinear plasma by sequence of relativistic electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2014)
The plasma wakefield excitation by long sequence of relativistic electron bunches is considered. It has been shown that taking into account ionization of the residual gas partially compensates resonance nonlinear detuning and the wakefield amplitude increases in comparison with the case of constant plasma density. Certain small excess of the plasma density on the resonant value also leads to focusing of more part of bunches, to extend the existence of the resonance and, as a result, to increase of the amplitude of the excited wakefield.